Füllung der Gesetzeslücken im schweizerischen Adhäsionsverfahren Beitrag zur Koordination des Straf- und Zivilverfahrensrechts im Adhäsionsverfahren nach Art. 122 ff. StPO - Klingler, Martin (sui generis Verlag, 2022)
Adhesion proceedings enable civil claims to be assessed in criminal proceedings. Its legal regulation in Art. 122 ff. StPO is, however, very rudimentary and incomplete. Jurisprudence and doctrine have so far hardly addressed the incompleteness of the procedure or the related coordination deficit of criminal and civil procedural law. The thesis shows how legal gaps in adhesion proceedings can be filled and how criminal and civil procedural law can be coordinated, as it were. The thesis shows which guiding principles are decisive for the filling of gaps. It explains how to deal with collisions between criminal and civil procedural law. With the help of the developed method, the work then provides concrete proposals for solutions to specific procedural questions.